Like in Korean English speech. Issue 4 (11th March 2021) - Rüdiger, Sofia
Abstract: This article focuses on the use of like by Korean speakers of English. South Korea is a fascinating context for world Englishes studies: English is generally learned as a foreign language, but deep political and historical ties facilitate a high visibility and prominent status of the language in Korean society. In this study, the use of like by Korean speakers of English with particular attention to discourse‐pragmatic aspects are investigated with the help of the Spoken Korean English Corpus (SPOKE). Like is a high frequency item in SPOKE and clearly forms part of the Korean English repertoire across its functional range. Even though usage of like as discourse marker and particle is influenced by having spent time abroad and (self‐reported) English proficiency, it forms part of the repertoire of nearly all surveyed speakers. Quotative like has also found a place in the Korean English repertoire, albeit to a lesser degree.